(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2025)
Auditory learning plays a fundamental role in the development of preschool children. Through listening-based activities, children strengthen their language skills, memory, attention, and social-emotional abilities. This article explores the significance of auditory learning in early childhood education and highlights the benefits of auditory-based teaching methods.